Silane Based Radical Polymerization: Functionalized Homopolymers and Copolymers - Stefanac, Tomislav (My University, 1994)
This thesis presents a study on silane based polymerization in two parts.
In Part A, diphenylvinylsilane (1) underwent oligomerization with initiation by azo(bisisobutyronitrile) (AIBN) or benzoyl peroxide (BPO). The vinyl groups were preferentially consumed under either set of conditions. Several products were isolated; these included oligomers 3, an AIBN adduct 4, a dimer 5, and a trimer 6. The residual SiH moieties could be subsequently coupled hydrosilylatively with alkynes or vinylsilicones. The efficiency of the radical reactions was very low. 15% starting material was recovered even with 200 mol% of initiating radicals added to the reaction mixture. The relative radical reactivities of the two functional groups is discussed.
In Part B, 1 was radically copolymerized with styrene and methyl methacrylate (MMA). From the results of infrared and 1H NMR it was determined that 1 participated in copolymerization via a vinyl type polymerization and not in the form of a hydrogen-transfer type polymerization. Residual SiH groups along the backbone of the polymer remained reactive. A vinylsilicone and 9-vinylanthracene were grafted onto the copolymer from MMA and 1 by hydrosilylation and radical methods, respectively.
Keywords: silane, radical, polymerization, functionalized, homopolymers, copolymers, vinyl groups, oligomers